Anemia and blood boosting - Eichner, E. R. (2001)
Reviewed here are the three "anemias" of athletes. Sports anemia is a misnomer, a false anemia, a dilutional pseudoanemia. It results from expansion of baseline plasma volume, a cardinal adaptation of aerobic fitness. Footstrike hemolysis, better termed exertional hemolysis, is a trivial concern clinically, because it is mild, rarely depletes iron, and almost never causes anemia. Iron deficiency anemia, however, is a common cause of exertional fatigue among female athletes. Accordingly, this review keys on how to diagnose, treat, and prevent iron deficiency anemia. Aspects of blood donation are also covered. Finally, blood boosting is reviewed. Endurance athletes continue to use Epo and use other methods to boost blood and to disguise boosting. A new urine test for Epo, if used in year-round, unannounced testing, may curb the abuse of Epo in sports. Considering human nature, however, odds are some athletes will still cheat to win - or die trying. Key points: Sports anemia is a false anemia in athletes who are aerobically fit. Bursting of red blood cells during exertion almost never causes anemia. Iron deficiency anemia is common among female athletes. Exertional fatigue is the hallmark of mild anemia. Donating blood is altruistic but ergolytic. Blood boosting is risky but rampant.